Reformers and Revolutionaries in Modern Iran: By Stephanie Cronin, ed. (London and New York: Routledge, 2009. 316 pages.) (American Journal of Islam and Society, 2010)
One cannot think of politicized Islam in Iran without thinking of the IranianLeft’s formation and overall history. The awkward yet symbiotic relationshipbetween them continues to impact how political decisions are made,especially at the parliamentary level. Given the Left’s wide-ranging linkageswith surrounding regions, including the Causacus (early twentieth century)and the Arab Middle East (particularly during the 1970s), experts dealingwith those regions’ politics would benefit from this work. As one of theMiddle East’s strongest leftist movements before the 1980s, any discussionof neighboring revolutionary movements must at least consider it. Althoughthis book assumes familiarity with twentieth-century Iran’s secular politicsand might be considered too dense, its rather large bibliographic section ismeant to encourage individual intellectual pursuits.Many contemporary scholars of the Iranian Left agree on its adherents’general lack of critical self-reflection throughout the twentieth century.Reformers and Revolutionaries in Modern Iran offers a forum for criticalreassessments of organizational platforms along with constructive propositionsmeant to enhance the viability of left-leaning programs – especiallysocial-democratic initiatives. This latter point is crucial, because severalcontributors deliberately state the importance of rejuvenating the Leftthrough social democratic reformism. Historical examples are used to provethis option’s viability over the more “rigid” Marxist-Leninist and Stalinistexamples ...